Locking plate fixation versus intramedullary nail fixation for the treatment of proximal humerus fracture: a review - Gujar, Harshad S.; Yadav, Vijay; Tonde, Jeevan (International Journal of Research in Orthopaedics, 2026)
Proximal humerus fractures are among the most common fractures in the elderly population, with increasing incidence due to osteoporosis. Surgical management is required in displaced and unstable patterns, with locking plate fixation and intramedullary nailing being two commonly employed techniques. This review summarizes the principles, advantages, limitations, and clinical outcomes of these modalities. Locking plates provide stable fixation, particularly in complex and osteoporotic fractures, while intramedullary nails offer a minimally invasive option with reduced soft tissue trauma. Current evidence suggests comparable union rates and functional outcomes, although complication profiles differ. The choice of fixation should be individualized based on fracture pattern, bone quality, and surgeon expertise.